2007
DOI: 10.1007/s10888-007-9057-9
|View full text |Cite|
|
Sign up to set email alerts
|

Discrete choice models of labour supply, behavioural microsimulation and the Spanish tax reforms

Abstract: The aim of the present study is to show the potential of behavioural microsimulation models as powerful tools for the ex ante evaluation of public policies. We analyse the impact of recent Spanish income tax reforms upon efficiency and household and social welfare and study the effects of various (basic-income and vital-minimum) flat tax schemes. The analysis is performed using a microsimulation model in which labour supply is explicitly taken into account. Instead of following the traditional continuous appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 28 publications
0
20
0
4
Order By: Relevance
“…The two US studies (Eissa and Hoynes (2004) and Heim (2009)) discussed by Bargain et al found small employment elasticities for men (0.03 and 0, respectively), as did Aaberge et al (1999Aaberge et al ( , 2002 for Italy, Brink et al (2007) for Sweden, Labeaga et al (2008) for Spain, and a number of papers for Germany.…”
Section: How Responsive Are Men's Employment Decisions?mentioning
confidence: 78%
“…The two US studies (Eissa and Hoynes (2004) and Heim (2009)) discussed by Bargain et al found small employment elasticities for men (0.03 and 0, respectively), as did Aaberge et al (1999Aaberge et al ( , 2002 for Italy, Brink et al (2007) for Sweden, Labeaga et al (2008) for Spain, and a number of papers for Germany.…”
Section: How Responsive Are Men's Employment Decisions?mentioning
confidence: 78%
“…The main implications were: (i) a reduction of personal income taxes for the vast majority, especially for high income individuals, (ii) an increase of the progressivity of the PIT, but a reduction in the redistribution (due to the reduction of taxes). See Labeaga et al (2008) for more details.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they have to calibrate a "bargaining parameter" to fit household behaviour. On the other hand, Labeaga et al (2008) analyse the 1999 PIT reform and other reforms involving a flat tax, using the unitary model and estimating separate utility functions for single individuals and couples. In the current study, we opt for the latter methodology.…”
Section: Introductionmentioning
confidence: 99%
“…22 Of course, these wages are not representative of all non-employed persons, but they can provide some illustration.…”
Section: Gross Wage Predictions For Non-employedmentioning
confidence: 99%
“…Figure 13 is illustrative and focuses only on experienced subgroups of non-employed. Table 11 and table 12 show the mean predicted values and standard errors 22 Overall, 340 observations are used, 154 for women and 186 for men.…”
Section: Gross Wage Predictions For Non-employedmentioning
confidence: 99%